Quarantine nematode species and pathotypes potentially dangerous for domestic potato production: populations diversity and the genetics of potato resistance - N. V. Mironenko; T. A. Gavrilenko; A. V. Khiutti; O. S. Afanasenko (Вавиловский журнал генетики и селекции)
The review considers quarantine species and nematode pathotypes potentially dangerous for domestic potato production. Potatoes are affected by more than 30 types of parasitic nematodes, but the review focuses on the most harmful representatives of genera that cause great damage to potato production: Globodera, Ditylenchus, Nacob bus and Meloidogyne. Phytopathological and molecular methods of identification of species and pathotypes and the main achievements in studying the population variability of parasitic potato nematodes were analyzed. It was shown that due to the peculiarities of the life cycle of nematodes and lability of their genomes, the genetic variability of these organisms is very high, which creates a threat of forming new pathogenic genotypes of the parasites. The information about the intra- and interpopulation variability of nematodes is important for studying the ways of introduction and distribution of separate species, as well as for searching for the correlations of molecular markers with the pathotype. Phylogenetic studies based on modern data on genetic variability of populations have allowed to reveal species complexes in Globodera pallida (Stone) Behrens and Nacobbus aberrans (Thorne) Thorne & Allen (sensu lato), including cryptic species. The main components of successful protection preventing a wide distribution of parasitic nematodes are quarantine measures, agricultural techniques, biological methods of protection and cultivation of resistant cultivars. Special attention in the review is paid to the breeding of potato cultivars with durable resistance to various nematode pathotypes, because the cultivation of such varieties is the most ecologically safe and economically advantageous way to prevent epiphytoties. Currently, significant progress has been made in the genetic protection of potato cultivars, especially against cyst-forming nematodes. The review provides data on sources of potato resistance to parasitic nematodes identified in collections of wild and cultivated species. Data on identified R-gens and QTL of resistance that have been introduced into breeding varieties using different methods and approaches are analyzed. The literature data on the study of structural and functional organization of genes for resistance to potato cyst nematodes are given. The results of molecular research on revealing the polymorphisms of loci involved in the control of resistance to cyst and gall nematodes, the development of molecular markers of certain genes and their use in marker-assisted selection for developing of new resistant cultivars, including those with group resistance, are considered.